Growth and electrical properties of AlOx grown by mist chemical vapor deposition - Toshiyuki Kawaharamura; Takayuki Uchida; Masaru Sanada; Mamoru Furuta (AIP Advances, 2013)
Aluminum oxide (AlOx) thin films were grown using aluminum acetylacetonate (Al(acac)3) as a source solute by mist chemical vapor deposition (mist CVD). The AlOx thin films grown at temperatures above 400°C exhibited a breakdown field (EBD) over 6 MV/cm and a dielectric constant (κ) over 6. It is suggested that residual OH bonding in the AlOx thin films grown at temperatures below 375°C caused degradation of the breakdown field (EBD). With FC type mist CVD, the reaction proceeded efficiently (Ea = 22–24 kJ/mol) because the solvent, especially H2O, worked as a stronger oxygen source. The AlOx film could be grown at 450°C with a high deposition rate (23 nm/min) and smooth surface (RMS = 1.5 nm). Moreover, the AlOx thin films grown by mist CVD had excellent practicality as insulators because the gate leakage current (IG) of the oxide thin film transistor (TFT) with an IGZO/AlOx stack was suppressed below 1 pA at a gate voltage (VG) of 20 V.